FGF5 Regulates Schwann Cell Migration and Adhesion - Chen, Bing; Hu, Rong; Min, Qing; Li, Yankun; Parkinson, David B.; Dun, Xin-peng (Frontiers in Cellular Neuroscience, 2020)
The fibroblast growth factor family polypeptides play key roles in promoting tissue regeneration and repair. FGF5 is strongly up-regulated in Schwann cells of the peripheral nervous system following injury; however a role for FGF5 in peripheral nerve regeneration has not been shown up to now. In this report, we examined the expression of FGF5 and its receptors FGFR1-4 in Schwann cells of the mouse sciatic nerve following injury, and then measured the effects of FGF5 treatment upon cultured primary rat Schwann cells. By microarray and mRNA sequencing data analysis, RT-PCR, qPCR, western blotting and immunostaining, we show that FGF5 is highly up-regulated in Schwann cells of the mouse distal sciatic nerve following injury, and FGFR1 and FGFR2 are highly expressed in Schwann cells of the peripheral nerve both before and following injury. Using cultured primary rat Schwann cells, we show that FGF5 inhibits ERK1/2 MAP kinase activity but promotes rapid Schwann cell migration and adhesion via the upregulation of N-cadherin. Thus, FGF5 is an autocrine regulator of Schwann cells to regulate Schwann cell migration and adhesion.